In vivo performance of lean bioabsorbable Mg–Ca alloy X0 and comparison to WE43: Influence of surface modification and alloying content - L. Berger; S. Dolert; T. Akhmetshina; J.-P. Burkhard; M. Tegelkamp; A.M. Rich; W. Rubin; S. Darwiche; G. Kuhn; R.E. Schäublin; B. von Rechenberg; B. Schaller; et al. (Bioactive Materials)
Magnesium alloys present a compelling prospect for absorbable implant materials in orthopedic and trauma surgery. This study evaluates an ultra-high purity, lean magnesium–calcium alloy (X0), both with and without plasma electrolytic oxidation (PEO) surface modification, in comparison to a clinically utilized WE43 magnesium alloy. It is shown that the mechanical properties of X0 can be tuned to yield a high-strength material suitable for bone screws (with an ultimate tensile strength of 336 MPa) or a ductile material appropriate for intraoperatively deformable plates (with an elongation at fracture of 24 %). Four plate-screw combinations were implanted onto the pelvic bones of six sheep without osteotomy for 8 weeks. Subsequent analysis utilized histology, micro-computed tomography, and light and electron microscopy. All implants exhibited signs of degradation and hydrogen-gas evolution, with PEO-coated X0 implants demonstrating the least volume loss and the most substantial new-bone formation on the implant surface and surrounding cancellous bone. Furthermore, the osteoconductive properties of the X0 implants, when uncoated, exceeded those of the uncoated WE43 implants, as evidenced by greater new-bone formation on the surface. This osteoconductivity was amplified with PEO surface modification, which mitigated gas evolution and enhanced osseointegration, encouraging bone apposition in the cancellous bone vicinity. These findings thus indicate that PEO-coated X0 implants hold substantial promise as a biocompatible and absorbable implant material.